Cultural Ecology and Environmental Education: Lesson Learned from Baduy Indigenous Community - Bagja Waluya; Elly Malihah; Mamat Ruhimat; Erlina Wiyanarti (Indonesian Journal of Geography, 2023)
This research investigated culturally-generated abilities and skills in the frame of human adaptation and environmental education. Under qualitative approach, this research implemented phenomenological research method that seek to understand the situation that occurs locally to certain group. Data collection was done through observation and interview with four key informants involving indigenous community leaders, community members, and formal education practitioner. Additional informants were taken from snowball sampling technique from whose accounts were elaborated until data saturation achieved. Validity and reliability of data were carried through member check and data triangulation. Data analysis process follow three sequential phases, namely data reduction, display, and drawing conclusion. Findings of research were grouped into three sections, namely a) cultural ecology of Baduy indigenous community; b) environmental education based on local wisdom of Baduy people; and c) pedagogical experience on local wisdom-based learning.